POTENTIAL AND ECONOMIC VALUE OF MARINE TOURISM OBJECT IN TUNDA ISLAND, SERANG BANTEN DISTRICT - Arum Bisyawal, Tommy
Almost 70% of Indonesia's territory is waters that have potential of natural resources and biodiversity which can be developed to increase the economic value, one of which is tourism potential. Tunda Island, Serang, Banten has diverse coral reef resources. The aims of the research are to identify the potential of coral reef ecosystems, calculate the carrying capacity, suitability of tourist objects, and estimate the economic value of marine tourism objects on Tunda Island. The study was conducted in the northern part of Tunda Island. Determination of observation stations using the Purposive Sampling method so that three research stations are obtained and are expected to represent the condition of the coral reef of Tunda Island. This study uses the Line Intercept Transect (LIT) method to obtain coral reef conditions, and the Underwater Visual Cencus (UVC) method to calculate the type of fish on the LIT transect. Measuring the quality of the aquatic environment includes temperature, brightness, strong currents, and depth. Calculation results from LIT, UVC, and water quality are included in the Tourism Suitability Index (IKW). The calculation of the economic value of the Tunda Island marine tourism object uses the Individual Travel Cost Method (ITCM) method with a Willingness To Pay (WTP) approach. The results showed the condition of coral reefs in the northern region of Tunda Island included in the medium category with the value of live coral cover namely station one 26%, station two 33.5%, and station three 31.4%. The northern region of Tunda Island has a tourist suitability index (IKW) which falls into the appropriate category (S2). Based on the carrying capacity of the northern part of Tunda Island, it can accommodate as many as 79 people per day for an area of 79.2 hectares. The value of Tunda Island tourism benefits is by using the Individual Travel Cost Method, which amounts to IDR 50,532,456 in 2017 with the Total Benefit or economic value of the Tunda Island area amounting to IDR 9,636,000,000 / year.